Immunohistochemical investigation of neuroendocrine component in prostate adenocarcinoma. - Prokopyk, O. V.; Kuryk, O. G.; Andreyev, M. D. (Морфологія / Morphologia / Morfologìâ, 2010)
A purpose of current research was to investigate the neuroendocrine component of prostate adenocarcinoma. The immunohistochemical investigation with using markers of neuroendocine differentiation – chromogranin A and neuron-specific enolase was performed. The neuroendocrine differentiation in light-cell adenocarcinoma is more expressive comparing with poorly dark-cell adenocarcinoma, and the neuroendocrine differentiation in moderately differentiated adenocarcinoma is more expressive comparing with poorly differentiated adenocarcinoma.